Systemic Innovation In The Making: The Social Productivity of Cartographic Crisis and Transitions in the Case of SEEIT - Nicolaj Tofte Brenneche (Copenhagen Business School (CBS), 2013)
The long term transition to sustainable energy systems is already having an impact on how energy research and innovation is being organized. With ambitious European and national goals for energy system transitions, a new transition complexity challenges established domains of expertise and other established actor domains. Thus, system transition complexity opens up for a broad range of new relational problems which transgress established definitions of expert domains and which areas of expertise `belong' to energy research and which actors are relevant for energy research and innovation. As an example hereof, the long term prospective of transformed energy systems actualizes a need for combining expert domains and actors within energy efficient buildings with expert domains and actors within the modeling, planning and management of energy systems of various kinds. Many other examples could be listed illustrating how energy research as a complex field of knowledge production and innovation confronts a new, open transition complexity, which transforms the landscapes of energy research.
hdl:10398/8784
Keywords: 650